Using a treatment diary to improve the medication adherence in patients with chronic myeloid leukaemia. (July 2019) - Santoleri, Fiorenzo; Lasala, Ruggero; Logreco, Andrea; Ranucci, Elena; Costantini, Alberto
Purpose: The aim of this study was to verify whether the distribution of a treatment diary by a pharmacist could influence the adherence to oral treatment with imatinib, nilotinib, and dasatinib in patients with chronic myeloid leukaemia. Methods: The level of adherence was calculated using the received daily dose/prescribed daily dose ratio and compared between patients who used a diary and those who did not. Results: Forty-four (35.8%) of 123 patients with chronic myeloid leukaemia completed the diary: 20 (45.4%) receiving imatinib, 17 (38.6%) receiving nilotinib, and seven (15.9%) receiving dasatinib. Treatment adherence with the diary calculated using received daily dose/prescribed daily dose method was 93.6% (imatinib 94.9%, nilotinib 91.1%, and dasatinib 95.8%). Adherence during the period without a diary was 86.5% (84.9, 87.4, and 90%). Adherence was significantly greater with than without a diary (p < 0.0001). Conclusions: The findings of this study that, in the case of chronic diseases, direct pharmacist–patient contact is important in order to maintain high levels of adherence, and a treatment diary is a valid means of doing this. According to these data, it is necessary to support similar patient-oriented programmes in order to ensure high levels of adherence and optimize drug management.